2014
DOI: 10.3892/ol.2014.2598
|View full text |Cite
|
Sign up to set email alerts
|

Smac/DIABLO expression in human gastrointestinal carcinoma: Association with clinicopathological parameters and survivin expression

Abstract: Lack of apoptosis is a key factor in carcinogenesis and tumor progression. Survivin is a member of the inhibitor of apoptosis protein (IAP) family. Second mitochondria-derived activator of caspases/direct inhibitor of apoptosis-binding protein with low pI (Smac/DIABLO) is an antagonist of IAPs. Recently, Smac/DIABLO was identified as a potent therapeutic target. However, the clinical significance of Smac/DIABLO in gastrointestinal carcinomas remains unclear. In the present study, Smac/DIABLO expression was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…We observed that nuclear survivin expression was more frequent in low-grade and early-stage IGCs in comparison to high-grade and advanced-stage IGCs. In the same line, Shintani et al (2014) found a relationship between the nuclear expression of survivin and well/ moderate differentiated gastric tumors and suggested that this nuclear expression is involved in promoting cell proliferation. Meanwhile, in contrast to Shintani et al, (2014) who did not find an association between sex and survivin expression, our data revealed a correlation between survivin positivity and expression with the male sex.…”
Section: Discussionmentioning
confidence: 82%
“…We observed that nuclear survivin expression was more frequent in low-grade and early-stage IGCs in comparison to high-grade and advanced-stage IGCs. In the same line, Shintani et al (2014) found a relationship between the nuclear expression of survivin and well/ moderate differentiated gastric tumors and suggested that this nuclear expression is involved in promoting cell proliferation. Meanwhile, in contrast to Shintani et al, (2014) who did not find an association between sex and survivin expression, our data revealed a correlation between survivin positivity and expression with the male sex.…”
Section: Discussionmentioning
confidence: 82%
“…The Paradox of Overexpression of the Pro-apoptotic Protein SMAC/Diablo in Cancer We (Figure 1) and others [16][17][18][19][20]35 have demonstrated overexpression of SMAC/Diablo in many types of cancer. This is unexpected in view of the pro-apoptotic activity of the protein, which promotes caspase activation by binding IAPs.…”
Section: Discussionmentioning
confidence: 89%
“…15 SMAC/Diablo was found to be overexpressed in some cancers and downregulated in others. For instance, the expression levels of both SMAC/Diablo mRNA and protein were reduced in hepatocellular carcinoma cells, as compared to normal hepatic tissue, 16 whereas higher levels were reported in cervical cancer, 17 lung, ovarian, and prostate carcinomas, gastric carcinomas, 18 renal cell carcinoma, 19 and different types of sarcoma. 20 The observation that SMAC/Diablo is overexpressed in cancer cells despite its role in promoting cell death suggests it might possess a new non-apoptotic function that has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the process of malignant transformation of colonic tissues into CRC includes alterations in the expression and/or activity of a number of cell death-related genes, molecules, and pathways leading to dysregulation and decrease in cell death rates. In cases of apoptosis, the most commonly reported alterations concern the TP53 , bcl-2-like protein 4 ( BAX ) [115,116], BCL-2 [96] p53 upregulated modulator of apoptosis PUMA ( BB3 ) [117], cellular caspase 8 (FLICE)-like inhibitory protein ( CFLAR ) [118], the X-linked inhibitor of the apoptosis protein ( XIAP ) [119], cellular inhibitor of apoptosis 2 ( CIAP2 ) [120], the baculoviral inhibitor of apoptosis repeat-containing 5 SURVIVIN ( BIRC5 ), and second mitochondrial derived activator of caspases ( SMAC ) genes [121,122]. In addition, marked changes in the expression of the necroptosis specific RIPK1 and RIPK3 molecules in CRC tissues have recently been published [109].…”
Section: Cell Deathmentioning
confidence: 99%